Development of Interactive Learning Media Through the Problem Based Learning Model to Improve Students' Mathematical Communication and Self Regulated Learning Skills - Mariani Sitanggang; Mulyono Mulyono; Sahat Saragih (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
This research seeks to (1) develop valid, (2) practical, and (3) effective interactive learning materials utilizing the Problem-Based Learning model. Conduct research, (4) evaluate the impact of integrating interactive learning media into the Problem Based Learning model on students' mathematical communication skills, (5) assess the development of students' self-regulated learning abilities, and (6) examine the answer process employed by students. students to pass an exam of their mathematical communication skills. This development investigation employed the Thiagarajan, Semmel, and Semmel 4D models (Define, Design, Develop, Disseminate). Participants in this study were eighth-grade pupils from SMP N 1 Bandar. The outcomes of research comprise interactive learning media such as worksheets, lesson plans, mathematical communication assessments, and self-regulated learning questionnaires. The findings of the study indicated that (1) the interactive learning materials created using the Problem Based Learning approach remained valid during trial two, (2) practice was acquired during trial two, and (3) the intervention was successful during trial two. Using interactive learning media and the Problem Based Learning model, students' mathematical communication skills were enhanced in trial II. Self-development among students—media-controlled learning. An increase in interactive learning was observed in trial II when the Problem Based Learning model was implemented.